Wildfire evolution and response to climate change in the Yinchuan Basin during the past 1.5 Ma based on the charcoal records of the PL02 core. (1st August 2020) - Shi, Yulan; Pan, Baolin; Wei, Mingjian; Li, Xinling; Cai, Maotang; Wang, Junping; Xu, Xiangke; Hu, Jianmin; Shi, Wei
Abstract: Wildfire activity is an important part of natural ecosystems and is strongly influenced by climate and vegetation changes. Given this, the reconstruction of wildfire history is crucial to understanding the interrelationships between past climate change and fire dynamics, especially in terms of revealing past climate change characteristics during particularly important periods. In this study we employed a macro-charcoal sequence to reconstruct the wildfire history in the Yinchuan Basin (an arid and semi-arid region in China) during the past 1.5 Ma. The responses of wildfire activity to climate and vegetation changes were compared with other obtained environmental indices such as magnetic susceptibility, pollen in the terrestrial basin core (the PL02 core), and δ 18 O in the marine core (LR04). The results confirmed that macro-charcoal records are an effective and sensitive indicator of environmental evolution in arid and semi-arid areas. The peak values of charcoal concentration and charcoal flux generally occurred during climate transition periods, especially in the transition period from humid to drought conditions (specifically in the MIS41-MIS40, MIS39-MIS38, MIS19-MIS18, MIS17-MIS16, MIS15-MIS14, MIS11-MIS10, MIS9-MIS8, and MIS3-MIS2 time intervals). Furthermore, we found that the biomass burned in wildfires (i.e., the high biomass burned as indicated by the peak levels of charcoal concentration) was controlled by the amount of vegetation, while the occurrence of wildfires was related to climate fluctuations. In addition, some Milankovitch cycles (such as 100-ka cycles, 40-ka cycles, and 20-ka cycles) were evident in the charcoal records, thus indicating that the main driving force of wildfire activity in the Yinchuan Basin was climate change caused by variations in the Earth's orbit. Among these, the 40-ka cycles disappeared after 0.72 Ma, accompanied by changes in wildfire activity characteristics. We also discovered that the 400-ka cycles were stable throughout time. This study provides reliable evidence for some remarkable climate events, including the Mid-Pleistocene Transition (MPT) and the Mid-Brunhes Event (MBE), from the charcoal records in the Yinchuan Basin (an arid and semi-arid region in the mid-latitudes of the Northern Hemisphere). Highlights: Wildfire evolution and its response to climate change were examined in the Yinchuan Basin during the past 1.5 Ma. The driving force of fire activity is climate change caused by variations in the Earth's orbit. The characteristics of fire activity are influenced by vegetation and climate change. Intense fire activity occurs during climate transition periods. Some remarkable climate events (i.e., the MPT and MBE) are reflected in the fire activity.